RETRACTED: Ahmad et al. Phytomedicine-Based Potent Antioxidant, Fisetin Protects CNS-Insult LPS-Induced Oxidative Stress-Mediated Neurodegeneration and Memory Impairment. J. Clin. Med. 2019, 8, 850 - Ashfaq Ahmad; Tahir Ali; Shafiq Ur Rehman; Myeong Ok Kim (Journal of Clinical Medicine, 2026)
The Journal retracts the article “Phytomedicine-Based Potent Antioxidant, Fisetin Protects CNS-Insult LPS-Induced Oxidative Stress-Mediated Neurodegeneration and Memory Impairment” [...]